Curriculum Management in Education Quality Improvement: A Catholic School-based Solution - Yuda, Yohanes (Educationist: Journal of Educational and Cultural Studies, 2022)
This study aims to describe the management education curriculum in quality improvement: (1) curriculum planning, (2) organizing the curriculum, (3) the implementation of the curriculum, and (4) supervision of curriculum in improving the quality of education in Secondary School the First Catholic 1 WR. Soepratman Samarinda. This research was conducted with a qualitative approach and data collection techniques by observation, documentation, and interview. Data analysis was performed with the following phases: compiling, linking, reduction, presentation, and conclusion. The results showed that: 1) Curriculum planning the school has always emphasized the importance of the aspects of the vision and mission of the school, the changes that occur in the educational process, adapted to the program of the national education curriculum and local curriculum, as well as the circumstances and needs of the school. The stages of planning, namely: planning meeting of the curriculum, evaluation of the implementation of the curriculum, planning and discussing the program curriculum, setting policies and agreements program-the program curriculum. Planning is done at the beginning of the year learning with the involvement of the foundation, the school committee, the school superintendent, the principal, the vice principal, teachers, and administrative staff of the school. 2) Organizing the curriculum of the provision of duties and authority by the principal to the coordinator of the curriculum, namely the deputy principal and the senior teachers to supervise the learning process. 3) The implementation of education curriculum is implemented in accordance with the draft and the academic calendar as well as involving all members of the school community. 4) Supervision of the curriculum is done by checking the learning tools such as teaching materials and planning the Implementation of the Teaching and learning media. The management of the curriculum that can better achieve the goal namely achievement and the directionality of the learning activities are run effectively and efficiently, building the character of students, improving student achievement, and improving the quality of education. Expected cooperation, communication, and involvement of all members of the school community in the management of the curriculum so that the achievement of quality.